Eksistensi Ilmu Qiraat Di Kalangan Mahasiswa Bahasa Arab Uinsu Stambuk 2020 - Syafrianda; Muhammad Alfiansyah; Dedi Masri; Nuzul Ramadhona MK (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The science of qira'at has a very important role among Muslims, because with the knowledge of qira'at it is very helpful and understands how to read the Koran properly and correctly. This study explains the existence of the science of qira'at among Arabic language students at the State Islamic University of North Sumatra in 2020. The type of research in this paper is descriptive qualitative. Data collection techniques used by way of interviews and also with various sources both from relevant books and journals. The results of this study indicate that the science of qiraat can be said to exist quite well among students of the STambuk 2020 Uinsu Arabic language education, because more respondents know and understand the basic concept of qiraat.